Aplikasi Pemesanan Undangan Pernikahan Digital (Web & Vidieo) Hawa Percetakan Berbasis Android - Wijaya, Anggi Hadi; Ipriadi, Ipriadi; Fitri, Wahyu (Jurnal Sains dan Teknologi (JSIT), 2024)
Accepting orders for digital wedding invitations and video invitations at the printing press is very simple, namely using social media Whatsapps, Youtube, Facebook and Telegram. Orders received are managed separately from payment and reporting, making it very difficult for consumers and printing companies to manage them. With this Android-based ordering application, it can make it easier to manage orders for digital and video wedding invitations in the printing press. This system was built using Android Studio with the help of the HTML programming language.